The Influence of Hot Forming Process on the Microstructure and Corrosion Performance of Recycled Magnesium Alloys - J., Alias (2017)
Introduction •Usage & Recyclability for Magnesium Alloy –Challenges •Deformation mechanism of magnesium and its alloys •Casting and Hot Forming-Quenching (HFQ) process •Corrosion of magnesium alloy